Energy drinks consumption in Erbil city: A population based study - Asaad, Yassin A. (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Energy drinks have become increasingly prevalent among young adults and adolescents in recent years, particularly young students and athletes who see the consumption of energy drinks as an easy and quick way to boost academic and athletic performance. This study was conducted to determine the prevalence of consumption of energy drinks in a sample of adolescent and adults in Erbil city as well as perceived benefits and its health hazards. Methods: A convenience sample of 600 individuals from different sectors and social groups of Erbil city was selected. Data was obtained through direct interview. The data was managed through SPSS program version 18, using appropriate statistical tests. Results: The prevalence of energy drinks consumption among the study population was 42.7%, especially adolescents and young adults (those ≤ 25 years) and was more common among males than females (55.7% and 29.8%, respectively). The main reasons for its consumption were related to getting energy and improving the mood and performance (66.0% and 30.4%, respectively). 62.7% of participants think that it is harmful and could have adverse effects such as heartbeat irregularity and blood pressure swinging, addiction, and osteoporosis (46.2%, 33.7% and 13.2%, respectively). Televisions were the major source of advertisement (71.45). A significant statistical association had been found between the age, gender and educational status of the participants and consuming energy drinks (P = 0.001, 0.001 and 0.002, respectively). Conclusion: Energy drinks consumption found to be highly prevalent in adolescents and young adults in Erbil city, which calls for review and regulating the sale of these drinks including adolescents’ education, raising community’s awareness, banning selling it in public places and increasing taxes.